2020
DOI: 10.1044/2020_jslhr-19-00397
|View full text |Cite
|
Sign up to set email alerts
|

Automated Phenotyping Tool for Identifying Developmental Language Disorder Cases in Health Systems Data (APT-DLD): A New Research Algorithm for Deployment in Large-Scale Electronic Health Record Systems

Abstract: Purpose Data mining algorithms using electronic health records (EHRs) are useful in large-scale population-wide studies to classify etiology and comorbidities ( Casey et al., 2016 ). Here, we apply this approach to developmental language disorder (DLD), a prevalent communication disorder whose risk factors and epidemiology remain largely undiscovered. Method We first created a reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Recent advances in data-driven approaches such as data mining algorithms and machine learning models have the potential to further accelerate progress in this research area, by automating the identification of cases with particular symptomatology in electronic heath records (e.g., automated phenotyping tool for DLD cases, APT-DLD: Walters et al, 2020 ; phenome risk classifier for stuttering: Pruett et al, 2021 ), the extraction of neural features from magnetic resonance imaging (MRI) data (e.g., toolbox for the automatic segmentation of Heschl’s gyrus, TASH toolbox: Dalboni da Rocha et al, 2020 ), the extraction of features in the genetic architecture of a trait (e.g., GWAS loci prioritization: Nicholls et al, 2020 ), and the integration of neuroimaging and genomic data to predict phenotypic outcomes (e.g., Shen & Thompson, 2020 ).…”
Section: Integrating Genetics Approaches Into Musicality-language Res...mentioning
confidence: 99%
“…Recent advances in data-driven approaches such as data mining algorithms and machine learning models have the potential to further accelerate progress in this research area, by automating the identification of cases with particular symptomatology in electronic heath records (e.g., automated phenotyping tool for DLD cases, APT-DLD: Walters et al, 2020 ; phenome risk classifier for stuttering: Pruett et al, 2021 ), the extraction of neural features from magnetic resonance imaging (MRI) data (e.g., toolbox for the automatic segmentation of Heschl’s gyrus, TASH toolbox: Dalboni da Rocha et al, 2020 ), the extraction of features in the genetic architecture of a trait (e.g., GWAS loci prioritization: Nicholls et al, 2020 ), and the integration of neuroimaging and genomic data to predict phenotypic outcomes (e.g., Shen & Thompson, 2020 ).…”
Section: Integrating Genetics Approaches Into Musicality-language Res...mentioning
confidence: 99%
“…The DLD case set was previously identified by applying the APT-DLD algorithm to the 3.5 million clinical records in Vanderbilt University Medical Center's EHR system called Synthetic Derivative, as part of the APT-DLD development efforts; the details were reported in Walters et al 30 The APT-DLD algorithm identified 6013 pediatric records as DLD cases with available ICD codes, dates of the ICD codes, and relevant demographic information (Table 1). This cohort of DLD cases was used as the input for the large-scale comorbidity analysis performed in the present study.…”
Section: Study Populationmentioning
confidence: 99%
“…[26][27][28][29] Developmental language disorder does not have a single unique diagnostic billing code; thus, to label DLD cases, we leveraged an existing electronic health record (EHR)-based tool with high positive predictive value (90%-95%) for DLD called the Automated Phenotyping Tool for Identifying Developmental Language Disorder (APT-DLD). 30 We then performed an enrichment analysis to identify comorbidities across the medical phenome. The aim of this study was to identify these clinically relevant comorbid conditions that co-occur with DLD using data-rich EHRs to better understand the epidemiological characteristics of DLD at a population level and potentially raise awareness of the DLD phenotype in the clinical community.…”
mentioning
confidence: 99%
“…While reliable phenotyping is currently available in biobanks and electronic health records for many health, cognitive, and psychiatric traits, speech-language and reading traits are generally underrepresented in these large-scale databases and are often superficially phenotyped ( Raghavan et al, 2018 ). Efforts are therefore underway to mine available speech-language phenotypes in existing electronic health records using sophisticated computational methods such as automated pipelines (e.g., for identifying cases with Developmental Language Disorder: Walters et al, 2020 ) and machine learning (e.g., for imputing stuttering cases: Pruett et al, 2021 ). Both approaches aim to decrease manual effort (e.g., clinical chart review) toward achieving the scales required for genetic investigations.…”
Section: Introductionmentioning
confidence: 99%